Ki Madhari: Tokoh Rurukan Adat Nabawadatala Desa Citengah - Ridwan Simon; Tati Narawati (Institut Seni Indonesia Denpasar, 2022)
The purpose of writing this article is to reveal the role of a figure in building and developing the Nabawadatala Rurukan Adat which is a forum for absorbing the aspirations of the community through various activities to improve the image, values, and cultural order as the implementation of the Sumedang Puseur Sundanese Culture (SPBS) program. The tri tangtu pattern which is used as a foothold in building and developing local culture is still relevant to be applied. By using an ethnographic approach and descriptive qualitative methods, various interesting phenomena related to the cultural and natural charm of Citengah Village are revealed, with the involvement of Ki Madhari as one of the community leaders trying to build the usefulness value of the richness of art and culture, as well as the geographical grace of beautiful nature. the results show that good governance with a humanist approach from a character is able to image values and cultural benefits into something of aesthetic and economic value.